Evaluation of the accountability of the achievement scholarship program in Pinrang Regency - Aslinda; Henni Zainal; Muhammad Ikramullah Akmal; Muh Luthfi Siraj (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
Policy evaluation plays a crucial role in improving the quality of government programs. Through these evaluations, the government can identify and prevent programs that could potentially harm the public, while also assessing whether such programs are worth continuing or expanding in the future. One of the programs that will be discussed in this study is the government policy in providing scholarships to outstanding students for underprivileged students to continue their education in higher education. This program is widely disbursed by the government through the provision of educational assistance both at the provincial, city, to district level. One of them, including in Pinrang Regency, has implemented a policy in the field of education regarding the provision of educational scholarships to outstanding students. However, based on the author's observations, it was found that this policy has shortcomings, namely there are still scholarships that are not on target, especially for scholarships for underprivileged communities and the lack of firmness of the implementing committee in collecting administrative requirements, there are problems that occur in the process of determining scholarship recipients, There are recipients who have the lowest GPA below 3.50, found in C Accredited Institute or College campuses.This research has a very important urgency for academics and government agencies as policy makers to conduct analytical studies onEvaluation of the Education Scholarship Program Policy for High-Achieving Students in Pinrang Regencyand as material for consideration in making decisions in the future. The aim of this research isto analyze how the form of the Evaluation of the Education Scholarship Program Policy for Outstanding Students in Pinrang Regency. This research is a type of qualitative research with a descriptive approach with the aim of describing all problems related to the government's program policies on the Evaluation of the Education Scholarship Program Policy for Outstanding Students in Pinrang Regency. The research results show that the effectiveness of the scholarship program in Pinrang Regency is influenced by several key factors, namely the number of implementing human resources, budget allocation, and the functionality of SOPs in program management. In terms of human resources (HR), the scholarship program management involves approximately 84 staff members spread across administrative units, supervisors, supervisors, and other technical teams.